2017
DOI: 10.7771/2157-9288.1160
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers’ Reflections on Design Failures and Use of Fail Words after Teaching Engineering for Two Years

Abstract: This mixed-methods study examines how teachers who have taught one or two units of the Engineering is Elementary (EiE) curriculum for two years reported on: students' responses to design failure; the ways in which they, the teachers, supported these students and used fail words (e.g. fail, failure); and the teachers' broad perspectives and messages to students about failure. In addition, the study explores how strategies, perspectives, messages, and fail word use may change after two years of engineering instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Students should work to provide solutions to design tasks by identifying problems and generating possible ideas, collaboratively planning and testing their solutions using existing scientific knowledge, evaluating and communicating their findings, and optimizing their original models (Brophy, Klein, Portsmore, & Rogers, 2008). Engineering design-based tasks differ from existing science curricular activities in that: (a) design problems require more complex, student decision-driven responses than typical teacher-guided scientific inquiries (Windschitl & Stroupe, 2017); (b) students must work collaboratively within constraints to develop testable and workable solutions (Johnson, Wendell, & Watkins, 2017;Lottero-Perdue & Parry, 2017;Van Haneghan, Pruet, Neal-Waltman, & Harlan, 2015); and (c) design problems lead to numerous possible solutions (Antink-Meyer & Meyer, 2016). We argue these divergences between design-and inquiry-based science instruction signify areas of risk for teachers learning to adopt engineering design to teach science.…”
Section: Engineering Design and Elementary Science Teachingmentioning
confidence: 99%
“…Students should work to provide solutions to design tasks by identifying problems and generating possible ideas, collaboratively planning and testing their solutions using existing scientific knowledge, evaluating and communicating their findings, and optimizing their original models (Brophy, Klein, Portsmore, & Rogers, 2008). Engineering design-based tasks differ from existing science curricular activities in that: (a) design problems require more complex, student decision-driven responses than typical teacher-guided scientific inquiries (Windschitl & Stroupe, 2017); (b) students must work collaboratively within constraints to develop testable and workable solutions (Johnson, Wendell, & Watkins, 2017;Lottero-Perdue & Parry, 2017;Van Haneghan, Pruet, Neal-Waltman, & Harlan, 2015); and (c) design problems lead to numerous possible solutions (Antink-Meyer & Meyer, 2016). We argue these divergences between design-and inquiry-based science instruction signify areas of risk for teachers learning to adopt engineering design to teach science.…”
Section: Engineering Design and Elementary Science Teachingmentioning
confidence: 99%
“…The adoption of a growth mindset is consistent with productive engagement in engineering design. Design failure (i.e., when a design fails to meet one or more criteria) is an expected event in iterative engineering design processes (Cunningham & Kelly, 2017; Lottero‐Perdue & Parry, 2017a). Experienced, informed designers “focus their attention on problematic areas of their potential solutions … while doing effective diagnostic troubleshooting” (Crismond & Adams, 2012, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study adds to the emerging body of work demonstrating that design-focused instruction can promote positive attitudes toward failure (Gerber & Carroll, 2012;Lottero-Perdue & Parry, 2017b;Royalty et al, 2012;Sadler et al, 2000). The idea of failure carries negative connotations in classroom contexts (Lottero-Perdue & Parry, 2017a) and can have debilitating effects on learners' emotions, expectancies of future success, and behaviors (Anderson & Jennings, 1980;Chase, 2011;Covington & Omelich, 1981;Ruble et al, 1976).…”
Section: Discussionmentioning
confidence: 80%
“…Likewise, a study exploring how adult students in design thinking classes apply design thinking in their work contexts found that one of the students' key take‐aways was comfort with failure and risk (Royalty, Oishi, & Roth, ). In another study, elementary school teachers who participated in a 2‐year engineering design curriculum became more comfortable using fail words during instruction and were more likely to apply the ideas of perseverance and learning from failure to domains outside of engineering (Lottero‐Perdue & Parry, ). A study of high school girls from marginalized communities found that fostering a safe and supportive maker environment enabled students to embrace a risk‐taking culture where failure was reframed as merely another iteration or draft (Ryoo et al, ).…”
Section: Literature and Backgroundmentioning
confidence: 99%